Pengaruh Penambahan Surfaktan pada Fermentasi Tandan Kosong Kelapa Sawit dengan Praperlakuan Uap Air Panas Bertekanan dengan Katalis Asam Maleat - Anita, Sita Heris; Ashrianis, Devi Nury; Fatriasari, Widya (Universitas Andalas, 2021)
Oil palm empty fruit bunch (OPEFB) has high potency to be converted into second generation bioethanol production. OPEFB pretreated liquid hot water (LHW) assisted maleic acid (MA) pretreatment was used as substrate in simultaneous saccharification fermentation (SSF). This pretreatment was conducted at 180 °C for 70 min by using 1.5% (w/v) MA acid concentration with material and liquid ratio of 1:14. Subsequently, the pretreated samples were fermented by addition of surfactant, polyethylene glycol (PEG) 4000 and amphiphilic lignin derivatives (A-LD) using Kluyveromyces marxianus InaCC Y119 yeast at temperature of 38 °C for 89 h. Before SSF, pretreated OPEFB was pre hydrolyzed by cellulase enzyme with enzyme loading 30 FPU/g at 50 °C for 3 h. Fermentation filtrate was taken at 0, 24, 48, 72, dan 89 h as much as 1.5 mL for reducing sugar and ethanol content determination. The surfactant addition can enhance reducing sugar and also ethanol content compared to control. The highest ethanol content of 1.251 g/L was found at fermentation of OPEFB pretreated MA with PEG 4000 surfactant at 89 h.